Reduced Number and Activity of Circulating Endothelial Progenitor Cells in Acute Aortic Dissection and Its Relationship With IL-6 and IL-17 - Huang, Zhenhua; Liu, Zhihao; Wang, Keke; Ye, Zi; Xiong, Yan; Zhang, Bin; Liao, Jinli; Zeng, Lijing; Zeng, Haitao; Liu, Gexiu; Zhan, Hong; Yang, Zhen (Frontiers in Cardiovascular Medicine, 2021)
This study investigates the alteration in function and number of circulating endothelial progenitor cells (EPCs) in patients with aortic dissection (AD), compared with hypertensive patients, and its possible mechanism. Thirty-four patients with acute aortic dissection (AAD) and 20 patients with primary hypertension were involved. Flow cytometry analysis was performed to detect the number of CD34+/KDR+ cells, and acetylated low density lipoprotein (ac-LDL) and lectin fluorescent staining method was applied to test the number of cultured EPCs. In addition, EPC migration and proliferation were measured, and plasma interleukin 6 (IL-6) and interleukin 17 (IL-17) levels were investigated. The number of circulating EPCs in the AAD group was lower than that in the non-AD group, and the proliferation and migration of circulating EPCs in the AAD group were lower than that in the non-AD group. In addition, the number, proliferation, and migration of circulating EPCs were significantly inversely correlated with the aortic dissection detection risk score (ADD-RS). More importantly, increased plasma IL-6 and IL-17 level was found in the AAD group, and the two inflammatory factors were inversely associated with the function and number of circulating EPCs in the AAD group. We first demonstrated that the number and function of circulating EPCs are reduced in the AAD group, which may be partly related to upregulated plasma IL-6 and IL-17. Our study provides novel insight on the underlying mechanism and potential therapeutic target of AAD.